An examination of the history and effect of American sex offense laws and offender registration - Shabat-Love, David (2012)
America's Sex Offense statutes and cases are some of the most controversial sections of modern law, both for the extreme sensitivity of their subject matter as well as the scope and application of those laws. This thesis is an analysis and overview of both the objective and subjective issues posed by the current state of those very laws: the subjective portion explored the development of current laws and the diverse attendant legal issues such as over-broadness and excessive or misdirected effect as compared to the Legislative and public intent which directly led to the development of these laws. Additionally a more objective study of their efficacy was conducted through the use of data regarding offense rates by locality. This objective data was procured from both the United States Census and Bureau of Justice statistics, which contained national averages such as the overall violent crime rate, and from the Florida Department of Law Enforcement Statistics and was supplemented with additional data from other academic sources. It is both the subjective conclusion and the interpretation of objective data that while the rate of sex offenses has lowered in recent decades this effect is a part of the overall trend of reduction in all violent offenses, and that the extreme stance of modern sex offense laws have arguably resulted in the net-negative of creating a class of individuals ostracized from all but other sex offenders who are virtually incapable of supporting themselves or at times of even finding legal habitation post-release. With little to no chance of a productive life, there is the strong possibility of recidivism and little incentive to avoid re-offending